Fabrication of non-volatile memory transistor by charge compensation of interfacial ionic polarization of a ferroelectric gate dielectric - Chakraborty R.; Pal N.; Pandey U.; Pramanik S.; Paliwal S.; Suman S.; Gupta A.; Singh A.K.; Swaminathan P.; Roy P.K.; Pal B.N. (My University, 2025)
Lithium niobate (LiNbO3) is a popular lead free perovskite ferroelectric materials, but its implementation as a gate dielectric for developing a ferroelectric thin film transistor (FeTFT) has not been investigated much due to its low band gap. Low band gap introduces high gate leakage current that results in very low retention time of the device. In this report a solution processed Li5AlO4/LiNbO3/Li5AlO4 stacked layer has been used as a gate dielectric of a metal oxide thin film transistor which reduces gate leakage current by four orders of magnitude with respect to the single layer LiNbO3 gate dielectric device. Besides, due to the ionic polarization of Li5AlO4 thin film that originated from the mobile Li+, charge compensation of the depolarization field has been nearly removed. By reducing these factors, it becomes possible to fabricate metal oxide based FeTFT that has retention time of 7 h which is ∼200 times higher with respect to the LiNbO3 only FeTFT. The ratio of On and Off state of FeTFT is ∼103 which retains ∼ 95% after 7 h of operation. The carrier mobility, ON/OFF ratio and subthreshold swing (SS) of this FeTFT are 2.9 cm2 V − 1 s − 1,7.2 × 104 and 328 mV.decade−1 respectively. © 2023 Elsevier Ltd